The Relationship of Latrine Quality with The Incidence of Worms in The Mekarsari Health Center Area, Lebak District - Sutomo, Omo; Rokayah, Yayah; Wasludin, Wasludin (JURNAL INFO KESEHATAN, 2024)
Family latrines, crucial for sanitation, impact community health. In 2019, Banten had 70.5% latrine use, below the national 72.3%. Poor sanitation causes diseases like helminthiasis, affecting many, especially children. This study aims to determine the relationship between the quality of family latrines and the incidence of helminthiasis in the Mekarsari Health Center area of Lebak Regency. The study used a cross-sectional design. The population included all families with goose-neck latrines in the Mekarsari Health Center area, with a sample size of 88 families. Data analysis was conducted in stages using the chi-square test at an alpha level of 0.05. The results showed that nearly all respondents (93.2%) were male, 96.6% were of productive age, most had low education levels (67%), and nearly all were non-civil servants (97.7%). The majority (73.9%) had a monthly income below the Lebak Regency minimum wage (< Rp 2,944,665). There were still 17% of families with low-quality latrines, and 9.1% of family members suffered from or were infected with helminthiasis (Ancylostoma duodenale). The relationship test results showed a significant relationship between latrine quality and helminthiasis incidence, with a p-value of 0.000 (p<α). The OR value was 63,000, meaning that families with low-quality latrines were 63 times more likely to suffer from or be infected with helminthiasis compared to families with high-quality latrines. The conclusion is that there is a relationship between the quality of latrines and the incidence of helminthiasis in the Mekarsari Health Centre Area, Lebak Regency. Serious efforts are needed to empower families through health education and assistance to encourage them to improve, construct, and maintain quality latrines to prevent helminthiasis infections.